The effects of executive functions on language control during Chinese-English emotional word code-switching - Zhang, Jiao; Fan, Lin (Frontiers in Psychology, 2023)
Executive functions (EFs) have great impact on language control indexed by language switch costs during production-based language switching. Yet, how they influence the language control during comprehension-based language switching between embodied first language (L1, Chinese) emotional words and less embodied second language (L2, English) emotional words is less understood. Employing an emotional priming paradigm, this study recruited Chinese-English bilinguals as participants, and used emotional faces and words as experimental materials to explore the effects of cool (i.e., inhibitory control ability, IC ability) and hot (i.e., emotional valence and emotional congruency) EFs on language switch costs (i.e., language control) of Chinese-English emotional word comprehension. The results showed larger language switch costs in the emotional congruent condition relative to emotional conflict condition, larger Chinese switch costs than English switch costs, and larger language switch costs for negative over positive emotional words in the emotional congruent condition. In addition, high-IC participants showed larger English switch costs for negative emotional words compared with low-IC participants. These results indicated that hot EF and the embodiment of language had an impact on both language control and the modulation of cool EF on language control, and the components of hot EFs interacted and jointly affected language control during language switching.